Case study: A finnish junior's eight-year road to cycling' World Tour - Given, J. (Haaga-Helia University of Applied Science, 2019)
The most elite level in road cycling is the World Tour. The World Tour is only reachable to a small number of exceptionally talented riders. Getting a contract with a World Tour team mostly rest on the performance and results made between the ages of 19-23. To get to this point most young riders will start from childhood with participation in athletics and dedicate many years to training, competition and improvement. The purpose of this study was to investigate how the participant`s training characteristics developed over an eight-year period, that saw the athlete develop from a 14-year-old junior mountain biker to a 22-year-old professional road cyclist, riding in the World Tour. This study attempts to provide a longitudinal description of the athlete`s maturation to elite status. The research questions asked how the athlete`s training had evolved between the years of 2012 - 2019 in terms of a) training volume, b) competition volume c) training intensity distribution and d) performance in competition. This study looks retrospectively at the athlete`s training to answer the question how did the athlete developed from a junior to World Tour professional? The study is based a retrospective analysis of a) self-reported training that the athlete made between the years of 2012 - 2019, b) publicly available race data that was collected from the web, and c) an interview with the athlete. In following sections is outlined how the data for each of the parts mentioned above were collected and how they relate to the aim and the research questions. Training volume and competition volume progressively increased over the eight years of the study. The athlete selected a pyramidal training intensity distribution based on time in heart rate training intensity zones. Annual top 10 finishes were compared with annual race days. Top 10 finishes were unlikely both in years where the athlete was the youngest rider and in between 2018 and 2019 when he was racing in top amateur level and World Tour. Yet the athlete was able to make several top 10 finishes in DN1 and one top 10 finish at the World Tour level.